Development, Implementation, and Evaluation of an Interdisciplinary Theory- and Evidence-Based Intervention to Prevent Childhood Obesity: Theoretical and Methodological Lessons Learned - ten Hoor, Gill A.; Plasqui, Guy; Schols, Annemie M. W. J.; Kok, Gerjo (Frontiers in Public Health, 2017)
Overweight and obesity in children and adolescents is seen as a global health challenge and a priority for prevention (1). To solve such a health issue, we need full understanding of the related health behaviors (and underlying beliefs), and understanding of the biological mechanisms that cause or can prevent the issue. However, for overweight and obesity, drawing a full picture of the exact problem (and the subsequent solution) is difficult. In this paper, we describe how we used Intervention Mapping to develop a theory and evidence-based prevention program targeting overweight and obesity and how we investigated the 1-year efficacy of this program on body composition and physical activity of adolescents. A helpful tool, theoretical, and methodological lessons learned are given from our attempt to contribute to solving the obesity problem.